KEBIJAKAN HUKUM PIDANA TERHADAP PENERTIBAN CAFE REMANG-REMANG - Luh Gede Yogi Arthani (Jurnal Hukum Saraswati (JHS), 2019)
The existence of dimly lit cafes is quite easy to find in Bali, even its existence in remote villages. A lot of commotion and crime that occurred in that place. In this research, we will discuss criminal acts that occur in dimly lit cafes and dim café control policies. The dimly-lit café is the place where criminal acts, namely the circulation of alcohol and prostitution activities. This activity is against the rule of law, and disturbs order in society, therefore its existence must be addressed. Tackling dimly lit cafes can be carried out with a penal policy and non-penal policy, namely by criminal law enforcement, licensing, community participation and a value approach.